Transforming Potential into Prosperity: A Phenomenological Study on Disability Empowerment and Islamic Values in Karangpatihan Village - Hidayat, Syarif; Mujahada, Kharis Syuhud; Rohmatullah, Dawam Multazam (Didaktika Religia, 2024)
This study aims to identify the strategy employed by the Village Head in developing the creativity potential of the disabled in Karangpatihan Village, integrating Islamic values in productive activities, and evaluating its implications for the social and economic welfare of the community. The research employs a qualitative approach, utilising a phenomenological methodology. The data were collected through observation, interviews and documentation, and subsequently analysed using triangulation techniques and the Miles & Huberman method. The findings of the study demonstrate that the Village Head engages with a range of stakeholders, including village officials and religious leaders, in the process of empowering the disabled. The strategy comprises skills training and the provision of business opportunities based on Islamic values, such as hard work, honesty, and mutual cooperation. The implications of this strategy are increased skills and economic participation of people with disabilities, a reduction of social stigma, and better social integration in society. The collaboration formed increases the spirit of mutual cooperation, which contributes to improving social and economic welfare in Karangpatihan Village.